2008
DOI: 10.1192/bjp.bp.107.039966
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of common mental disorders in general practice attendees across Europe

Abstract: BackgroundThere is evidence that the prevalence of common mental disorders varies across Europe.AimsTo compare prevalence of common mental disorders in general practice attendees in six European countries.MethodUnselected attendees to general practices in the UK, Spain, Portugal, Slovenia, Estonia and The Netherlands were assessed for major depression, panic syndrome and other anxiety syndrome. Prevalence of DSM–IV major depression, other anxiety syndrome and panic syndrome was compared between the UK and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
131
7
13

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(158 citation statements)
references
References 21 publications
7
131
7
13
Order By: Relevance
“…These figures are lower than those reported in the United States (US), where lifetime and annual prevalence rates for these disorders have been reported to be 29% and 11%, respectively (n = 9,282) (Kessler et al, 2005). However, King et al (2008) found no differences in the prevalence of anxiety disorders in the United Kingdom (UK) and Spain, the two countries with the highest prevalence rates in Europe. Despite the differences in prevalence rates among countries, there is little doubt that anxiety disorders are highly prevalent in Europe and more needs to be done to improve both detection and treatment.…”
Section: Introductioncontrasting
confidence: 52%
“…These figures are lower than those reported in the United States (US), where lifetime and annual prevalence rates for these disorders have been reported to be 29% and 11%, respectively (n = 9,282) (Kessler et al, 2005). However, King et al (2008) found no differences in the prevalence of anxiety disorders in the United Kingdom (UK) and Spain, the two countries with the highest prevalence rates in Europe. Despite the differences in prevalence rates among countries, there is little doubt that anxiety disorders are highly prevalent in Europe and more needs to be done to improve both detection and treatment.…”
Section: Introductioncontrasting
confidence: 52%
“…Local primary care studies linked depression and anxiety to younger ages 44,45 . A European study among general practice attendees showed that the peak age for major depression is young adulthood and the peak age for anxiety-spectrum disorders is midlife although the prevalence rates vary significantly among European nations 14 . Worldwide, half of all lifetime mental disorders in most studies begin by the mid-teens, and three-quarters begin by the mid-20s; severe disorders are typically preceded by less severe episodes that are rarely brought to clinical attention 46 .…”
Section: Discussionmentioning
confidence: 99%
“…A WHO study observed that the prevalence of having any psychiatric disorder in the previous year varied widely, from 4.3% in Shanghai to 26.4% in the United States 7 . Even among similar European nations, the prevalence of some mental illnesses differs from one country to another 14 . One US study indicated that no more than 41% of mature Americans who had a mental illnesses received mental health services in 2012 15 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The study on Psychological Problems in General Health Care (PPGHC), conducted across 14 countries, found that 14% of primary care attendees suffered from major depression; 4 a more recent study in six European countries found a lower rate of 8.5% in men. 5 Across all settings, best estimates for major depressive disorder are a 1-year prevalence rate of 4.1% (95% confidence interval [CI] = 2.4% to 6.2%), a lifetime risk of 6.7% (95%CI = 4.2% to 10.1%), and an incidence rate of about 9% over 12 months. 6 However, it should be noted that there are international differences in the epidemiology of depression, especially when comparing developing (low-income) with developed (high-income) societies.…”
Section: Introductionmentioning
confidence: 99%